Repairable Woven Carbon Fiber Composites with Full Recyclability Enabled by Malleable Polyimine Networks. Issue 15 (15th February 2016) - Taynton, Philip; Ni, Huagang; Zhu, Chengpu; Yu, Kai; Loob, Samuel; Jin, Yinghua; Qi, H. Jerry; Zhang, Wei
Abstract : Carbon‐fiber reinforced composites are prepared using catalyst‐free malleable polyimine networks as binders. An energy neutral closed‐loop recycling process has been developed, enabling recovery of 100% of the imine components and carbon fibers in their original form. Polyimine films made using >21% recycled content exhibit no loss of mechanical performance, therefore indicating all of the thermoset composite material can be recycled and reused for the same purpose.